Immobilisation von Weddellrobben - Bornemann, Horst; Plötz, Joachim (2005)
Behavioural studies on pinnipeds based on animal-mounted recording equipment rely on safe and easy to handle immobilisation methods to ensure successful and durable de-ployment of recording devices. Here we describe two different dose regimes for the drugs Ketamine, Xylazine, Diazepam and Yohimbine derived from 141 immobilisation procedures in Weddell seals carried out in the Antarctic between 1990 and 2003.